Shared cognitive intimacy and self-defence: two socio-emotional processes in problem solving - Hannula, Markku S. (NOMAD Nordic Studies in Mathematics Education, 2005)
This paper is an exploration into the social dimension of emotions. It is based on protocols of student problem solving sessions and comments from student interviews that are part of a three-year longitudinal ethnographic study of one classroom. Focusing on the role of emotions in social coordination of problem solving behaviour, this research extends into an area that has not received enough attention in previous research. Specifically, it will provide some insight into shared cognitive intimacy, which was occasionally experienced by students who constructed a solution to a problem together. Shared cognitive intimacy is an example of a situation where students can simultaneously fulfil both cognitive and social needs. Another phenomenon that was observed was how some students used defensive strategies to hide their lack of competency. These defensive strategies are often counterproductive in achieving the cognitive goals but they are functional in the service of social goals.